The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1001/jamaoto.2017.1768
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism Among Otolaryngology Patients vs General Surgery and Plastic Surgery Patients

Abstract: Most patients undergoing otolaryngology procedures are at low risk of VTE, indicating that guidelines for a low-risk population could be adapted to otolaryngology. Patients undergoing high-risk otolaryngology procedures should be considered as candidates for more aggressive VTE prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 26 publications
4
58
0
Order By: Relevance
“…Controlling for demographic and other operative factors, compared with general surgery (the specialty that treated the greatest number of patients in the study population), the present study found several surgical specialties to be independently associated with lower risk of VTE, including orthopedic surgery and plastic surgery (OR=0.496, p<0.001 and OR=0.141, p=0.001, respectively). The result of plastic surgery was consistent with adult literature 37. However, the result with orthopedic surgery was not expected and had not previously been reported.…”
Section: Discussionsupporting
confidence: 89%
“…Controlling for demographic and other operative factors, compared with general surgery (the specialty that treated the greatest number of patients in the study population), the present study found several surgical specialties to be independently associated with lower risk of VTE, including orthopedic surgery and plastic surgery (OR=0.496, p<0.001 and OR=0.141, p=0.001, respectively). The result of plastic surgery was consistent with adult literature 37. However, the result with orthopedic surgery was not expected and had not previously been reported.…”
Section: Discussionsupporting
confidence: 89%
“…In another study by Garritano et al that surveyed otolaryngologists, they reported a considerable variability among otolaryngologists in using intraoperative and postoperative thromboprophylaxis, they also reported 88.3% of otolaryngologists stated they would find thromboprophylaxis guidelines released by the American Academy of Otolaryngology ‐ Head and Neck Surgery to be helpful . A similar findings of heterogeneity in thromboprophylaxis utilization by otolaryngologists in UK were reported in a survey by Nash et al A recent study by Cramer et al evaluated the utility of American College of Chest Physicians guidelines (ACCP) using Caprini scores for risk stratification of patients undergoing otolaryngologic surgeries . They reported patients with a high risk of VTE based on Caprini score might benefit from chemoprophylaxis; however they also observed a higher risk of bleeding in patients with high Caprini score which they attributed to using anticoagulants.…”
Section: Discussionmentioning
confidence: 79%
“…This means pharynx and larynx were the only surgeries associated with a high risk of DVT and PE, as well as a high readmission risk. Cramer et al in their study that used data from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) identified a subset of high‐risk procedures within otolaryngology that included free or regional tissue transfer, laryngectomy, composite resection, skull base surgery, and incision and drainage . Lee et al also reported that a higher risk of VTE was associated with major head and neck surgeries .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations